3rd International Conference on Interactive Computer aided Blended Learning - ICBL2009 - for Papers, Call (International Journal of Advanced Corporate Learning (iJAC), 2009)
This interdisciplinary conference aims to focus on the exchange of relevant trends and research results as well as the presentation of practical experiences gained while developing and testing elements of interactive blended learning. Therefore pilot projects, applications and products will also be welcome.